Pengaruh Lama Penyimpanan Ikan Sarden Kemasan Kaleng terhadap Kadar Logam Pb dan Cu - Refilda Suhaili (CHEMPUBLISH JOURNAL, 2020)
ABSTRACT Canned sardines (Sardinella sp.) are very practical because they can be stored for a long time and can reduce contamination of bacteria and microorganisms from outside. However, direct contact with canned packaging for a long time can cause heavy metal contamination. Therefore, heavy metal concentrations of Pb and Cu from canned sardines (Sardinella sp.) were determined by Atomic Absorption Spectrophotometry (AAS) method. Samples of canned sardines (Sardinella sp.) digested using a mixture of concentrated HNO3 and 15% H2O2 (3:1). The samples tested were canned sardines with a storage time of 36 months (A), 18 months (B) and 6 months (C) after production. The results of Pb metal analysis of canned sardines (Sardinella sp.) in samples A, B, and C were 0.807 mg/L; 0.512 mg/L; and 0.387 mg/L. The concentration of Pb metal obtained in all samples exceeded the threshold value set by BPOM, at 0.3 mg/L. The concentration of Cu in samples A, B, and C were 2.718 mg/L; 1.996 mg/L; and 1.240 mg/L respectively . The concentration of Cu in all samples was still below the limit set by BPOM at 5 mg/L. The t-test statistic showed that there were significant differences in the concentration of Pb and Cu metals for the three types of samples (t-count>t-table). It can be concluded that storage time affects the concentration of Pb and Cu metals in canned sardines (Sardinella sp.). The longer sardines were stored in cans, the Pb and Cu metal concentrations would increase.